The Effect of Aegle Marmelos Shell Particles Size on The Mechanical Properties of Epoxy Matrix Composites as An Alternative Material For Motorcycle Disc Brake Pad - Firman Ocviansyah, Danny; Rusiyanto (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2024)
The particle size can effect the mechanical properties of composite materials. Variations in particle size will form different mechanical properties in the composite. The particle size variations used in this research are 100 mesh, 120 mesh, and 140 mesh. Making composites using a volume fraction of 30% aegle marmelos shell powder, 20% aluminum powder, and 50% epoxy resin using the hand lay-up method. This research design uses true experimental design with posttest-only design type, there is an experimental group (composite) and control group (Indoparts brand brake pads). Mechanical testing carried out is toughness / impact testing, rockwell-b hardness testing and wear testing. The highest toughness value was obtained in the composite with 140 mesh particle size variation of 0.01180 J/mm2. The highest rockwell-b hardness value was obtained in the 140 mesh particle size variation of 76.9 HRB. The hardness value is closest to the value of the Indoparts brand brake pad. This shows that the smaller the particle size, the hardness value increases. The most optimal wear test results were obtained in the 100 mesh particle size variation with a value of 5.7357 × 10-7 mm2/kg. This value is the closest value to the value of the Indoparts brand brake pad. So it can be concluded that aegle marmelos shell powder can be recommended as an alternative material for motorcycle brake pad.